Customers buying pattern on sportswear brand name clothing in Sibu / Khalid Abdul Hakim - Abdul Hakim, Khalid (2005)
For this project Paper (MKT 660) course, I have chosen "Customers Buying Pattern On Sportswear Name Clothing In Sibu" as a title of my study. Nowadays we find that most companies registered their product Brand in order to differentiate from others. The product with brand enables customers to identify when it makes available in the market. The owner of the brand will register their brand name with Pattern Department. Then it is legally protected, avoid imitators and only allow the usage of the brand with the concern of the owner.